Effect of Low-Salt Processing on Lipolytic Activity, Volatile Compound Profile, Color, Lipid Oxidation, and Microbiological Properties of Four Different Types of Pastırma - Kabil, Emre; Hazar Suncak, Fatma Yağmur; Kaban, Güzin; Kaya, Mükerrem (MDPI AG, 2025)
Pastırma is a traditional dry-cured meat product made from whole pieces of cattle or water buffalo carcasses. Sixteen or more types of pastırma can be produced from different parts of the carcass. This study investigated the effect of low salt processing (3% NaCl) on the lipolytic enzyme activity, volatile profile, color, lipid oxidation, and microbiological properties of commonly produced types of pastırma (kuşgömü, sırt, bohça, and şekerpare). In the study, 5% NaCl level was used as the control group. For all pastırma types, the pH changed between 5.5 and 6.0. The aw value was less than 0.90 for the pastırma types. The L* value increased when the salt level decreased from 5% to 3% (p < 0.05); however, the salt level did not affect the a* and b* values (p > 0.05). Reducing the salt level increased the neutral lipase activity and decreased the TBARS. As the salt level increased, the acid lipase activity increased in the bohça pastırma, and the phospholipase activity increased in the kuşgömü and sırt pastırma (p < 0.05). Furthermore, while Micrococcus/Staphylococcus constituted the dominant microbiota in pastırma types, a 5% salt level led to a decrease in the number of lactic acid bacteria. The volatile compounds were more affected by salt level than by pastırma type. The correlation analysis showed that there are some differences between 3% and 5% salt levels and the use of a 3% salt level increases the abundance of the compounds. The correlation analysis also revealed that there are differences between the pastırma types in terms of the volatile compounds and that kuşgömü pastırma differs from other pastırma types.